Impact of postoperative complications after cardiac surgery on long‐term survival. Issue 6 (9th March 2021) - Pahwa, Siddharth; Bernabei, Annalisa; Schaff, Hartzell; Stulak, John; Greason, Kevin; Pochettino, Alberto; Daly, Richard; Dearani, Joseph; Bagameri, Gabor; King, Katherine; Viehman, Jason; Crestanello, Juan
Abstract: Purpose: The impact of postoperative complications on long‐term survival is not well characterized. We sought to study the prevalence of postoperative complications after cardiac surgery and their impact on long‐term survival. Methods: Operative survivors ( n = 26, 221) who underwent coronary artery bypass grafting (CABG) ( n = 13, 054, 49.8%), valve surgery ( n = 8667, 33.1%) or combined CABG and valve surgery ( n = 4500, 17.2%) from 1993 to 2019 were included in the study. Records were reviewed for postoperative complications and long‐term survival. Propensity‐match analysis was performed between patients who did and did not have a postoperative complication. The associations between postoperative complications and survival were assessed using a Cox‐proportional model. Results: Complications occurred in 17, 463 (66.6%) of 26, 221 operative survivors. A total of 17 postoperative complications were analyzed. Postoperative blood product use was the commonest ( n = 12, 397, 47.3%), followed by atrial fibrillation ( n = 8399, 32.0%), prolonged ventilation ( n = 2336, 8.9%), renal failure ( n = 870, 3.3%), reoperation for bleeding ( n = 859, 3.3%) and pacemaker/ICD insertion ( n = 795, 3.0%). Stroke (hazard ratio [HR]: 1.55; 95% confidence interval [CI]: 1.36–1.77), renal failure (HR: 1.45; 95% CI: 1.33–1.58) and pneumonia (HR: 1.23; 95% CI: 1.11–1.36) had the strongest impact on long‐term survival. Long‐term survival decreased as the number of postoperative complications increased. Conclusions: Postoperative complications after cardiac surgery significantly impact outcomes that extend beyond the postoperative period. Stroke, renal failure, and pneumonia are particularly associated with poor long‐term survival.